2022
DOI: 10.3390/coatings12020245
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Bilayer Glass Coating on Porous Titanium Substrates with Enhanced Biofunctional and Tribomechanical Behavior

Abstract: The use of porous titanium samples fabricated by space-holder powder metallurgy with bioactive coatings has already been reported to prevent resorption of the bone surrounding the implant and improve osseointegration, respectively. However, the presence of pores as well as the poor adherence and the brittle behavior inherent to glassy coatings affect the service behavior of implants fabricated from these samples. Therefore, they need to be optimized. In this work, 50 vol.% of porosity titanium substrates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…The soluble ions (e. g., Si, Ca, and P) released by BG trigger differentiation of keratinocytes and upregulation of tight junction proteins (ZO-1, occludin, JAMÀ A, and claudin). [5] 58S-BG showed 90 % wound closure after 21 days of surgery in an in vivo study. [30] 45S5 BG-silica coating on AISI 316LSS deposited by sol gel method showed growth of HA layer, amorphous apatite and CaSiO 3 film on surface.…”
Section: Wound Healingmentioning
confidence: 90%
See 1 more Smart Citation
“…The soluble ions (e. g., Si, Ca, and P) released by BG trigger differentiation of keratinocytes and upregulation of tight junction proteins (ZO-1, occludin, JAMÀ A, and claudin). [5] 58S-BG showed 90 % wound closure after 21 days of surgery in an in vivo study. [30] 45S5 BG-silica coating on AISI 316LSS deposited by sol gel method showed growth of HA layer, amorphous apatite and CaSiO 3 film on surface.…”
Section: Wound Healingmentioning
confidence: 90%
“…Interestingly, bilayer coating of BG 45S5 (inner layer) and BG 1393 (outer layer) on porous Titanium (Ti) substrate exhibits efficient biomechanical yield strength, better osseointegra-tion and bioactivity. [5] For coating BGs on metallic biomaterials, several methods such as plasma spray, laser cladding, electrophoretic coating, biomimetic deposition and sol-gel are employed. [4] Although strong continuous adhesion between substrate and coatings remains a challenge, however tailoring BG compositions based on specific deposition techniques, can reduce failure and obtain adherent coatings.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the development of novel NPs, their surface modifications, enhanced biofunctional and tribomechanical behaviors, clinical performances, along with various nano-characterization methodologies in the dental field involving endodontics has been emphasized in a number of recent contributions as well [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. Studies have shown that the impact of nanomaterials for the treatment of various oral diseases in endodontics is showing fast progress.…”
Section: Discussion Of Literature Workmentioning
confidence: 99%
“…These results corroborate the effectiveness of the space holder technique as a fabrication process to tailor the desired porosity. The porous Ti disk used had an appropriate balance between porosity, which favors osseointegration, and the resulting biomechanical properties, as described in detail in [40,41,43,49,50]. The type of substrate used in the present manuscript shows an adequate biomechanical and biofunctional balance to replace small areas of cortical bone, matching the requirements of these tissues (E = 20-25 GPa y S y = 150-180 MPa).…”
Section: Characterization Of the Porous Cp Ti Substratesmentioning
confidence: 95%
“…Commercially pure (c.p.) porous titanium substrates (disks of ~12 mm diameter and 5 mm height) were prepared by the space-holder technique (SH), as previously reported in [37][38][39][40][41]. Briefly, ammonium bicarbonate (NH 4 HCO 3 ) was mixed with the c.p.…”
Section: Fabrication and Basic Characterization Of Porous Titanium Su...mentioning
confidence: 99%